The Activities of Local Authorities and Self-Government of the Republic of Belarus on Mitigation of Consequences of Chernobyl Disaster - Михайлович Демичев, Дмитрий (Teisė, 2018)
In article features of functioning of local governing bodies and self-government of Belarus on minimization of consequences of accident on the Chernobyl NPP are investigated, offers on expansion of competence of the local bodies which are carrying out soy activity on are proved it is radioactive the polluted territories.
Keywords: none